2012
DOI: 10.1038/gt.2012.9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting GRK2 by gene therapy for heart failure: benefits above β-blockade

Abstract: Heart failure (HF) is a common pathological end point for several cardiac diseases. Despite reasonable achievements in pharmacological, electrophysiological and surgical treatments, prognosis for chronic HF remains poor. Modern therapies are generally symptom oriented and do not currently address specific intracellular molecular signaling abnormalities. Therefore, new and innovative therapeutic approaches are warranted and, ideally, these could at least complement established therapeutic options if not replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…The relationship between up-regulated cardiac GRK2 levels and heart failure has been well established in animal models and in patients afflicted with different heart conditions (Harris et al, 2001;Reinkober et al, 2012). Moreover, it has been suggested that up-regulated expression of GRK2 in the vasculature might be associated with the pathogenesis of human essential hypertension (Gros et al, 2000;Cohn et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between up-regulated cardiac GRK2 levels and heart failure has been well established in animal models and in patients afflicted with different heart conditions (Harris et al, 2001;Reinkober et al, 2012). Moreover, it has been suggested that up-regulated expression of GRK2 in the vasculature might be associated with the pathogenesis of human essential hypertension (Gros et al, 2000;Cohn et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…[120][121][122] Of interest, the persistent β-adrenergic receptor kinase carboxyl-terminus cardiac expression allowed by AAV vectors could offer major advantages versus β-blocker therapy, namely the achievement of long-term therapeutic benefits after a single treatment and the lack of unspecific blocking of β-adrenergic receptor signaling pathway in other organs. 123 An alternative promising strategy stems from the use of AAV vectors to overexpress diffusible growth factors, which can extend their effect beyond the individually transduced cells. Multiple intramyocardial injections of an AAV9 vector expressing VEGF-B, a member of the VEGF family that selectively binds VEGFR-1 expressed on cardiomyocytes, remarkably improved cardiac function in rats after myocardial infarction, 124 in mice after aortic constriction, 125 and in dogs chronically instrumented to develop tachypacing-induced dilated cardiomyopathy.…”
Section: Gene Therapy Of Heart Failurementioning
confidence: 99%
“…GRK2 (formerly known as b-adrenergic receptor kinase 1) was found to be overexpressed in various brain and cardiovascular diseases, and is therefore considered to be a potential therapeutic target for these diseases [2][3][4][5]. Selective inhibition of GRK2 activity has been shown to increase therapeutic efficacies and decrease side effects [5,8].…”
Section: Introductionmentioning
confidence: 99%